2022
DOI: 10.1097/scs.0000000000009134
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaneurysms and Orthognathic Surgery: A Systematic Review and a Proposed Algorithm of Treatment

Abstract: This study aimed to gather existing evidence regarding the incidence, clinical presentation, and management of pseudoaneurysms (PA) after orthognathic surgery, identify the common blood vessels involved in PA, and propose a treatment algorithm based on current evidence. The protocol for this study was developed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols and was registered at the International Prospective Register of Systematic Reviews under the registrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Pseudoaneurysms have been reported to occur less frequently in mandibular osteotomies than in maxillary osteotomies (13,14). The first report of a pseudoaneurysm in a mandibular osteotomy was by Clark et al (15) in 1987 who reported a pseudoaneurysm following a mandibular vertical branch osteotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudoaneurysms have been reported to occur less frequently in mandibular osteotomies than in maxillary osteotomies (13,14). The first report of a pseudoaneurysm in a mandibular osteotomy was by Clark et al (15) in 1987 who reported a pseudoaneurysm following a mandibular vertical branch osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…AlQahtani et al (14) reported that CT angiography should be performed, and intervention should be indicated in the presence of epistaxis, significant facial edema, and pain after Le Fort I osteotomy. In our case, a pseudoaneurysm of the left STA was diagnosed using CT angiography after sudden hemorrhage and swelling.…”
Section: Discussionmentioning
confidence: 99%